Vapor chamber thermal performance: Partially heated with different heating areas at the center and supported by numerical analysis for the experimental setup - Varol, Yasin; Cosanay, Hakan; Tamdogan, Enes; Parlak, Murat; Senocak, Safak Melih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2025)
This paper presents the design of a partially heated Vapor Chamber (VC) system utilizing a passive cooling technique, analyzed under various inclination angles. The Finite Volume Method (FVM) is utilized to compare the results with experimental measurements conducted. Additionally, all results obtained with the tested VC are compared to a copper plate of identical dimensions to demonstrate the VC's impact on thermal management issues. The dimension of the copper VC is established as 56 x 56 mm2. Two distinct partial heating dimensions at the evaporator block, measuring 10 x 10 mm2 and 20 x 20 mm2, are evaluated under various heat flux loads. The study is further expanded to include varying temperatures between the evaporator block and the condenser block. While a chiller controls the temperature on the condenser block side, the power supply to the evaporator block is adjustable to facilitate heating. The inclination angle of the system is identified as an additional parameter for investigation, as it may influence the thermal performance of the vapor chamber due to gravitational effects. At the conclusion of the study, significant results indicated that a higher thermal resistance value was observed for a heating area of 10 x 10 mm2 for both VC and copper plate. The comparison between the copper plate and VC indicates a 7 % reduction in thermal resistance with VC across both selected heating areas. Furthermore, a higher temperature that increases proportionally with heat flux is observed in the case of the copper plate. The effect of inclination appears to be negligible for the parameters examined.
Keywords: Vapor Chamber; Thermal performance; Copper plate; Heat transfer; Electronic cooling